Pollen-inspired biopolymer-based multifunctional films - Seohan Yun; Taehoon Kim; Heeeun Choi; Fiorenzo G. Omenetto; Junyong Park (Proceedings of the National Academy of Sciences, 2025)
Naturally evolved materials and structures inspire next-generation sustainable manufacturing workflows and the development of intelligent, multifunctional, high-performance materials. However, integrating compositional and structural elements from diverse natural sources into a unified, high-performance platform remains a significant challenge. Here, we present a scalable strategy for creating robust, tunable, multifunctional surfaces by seamlessly integrating sunflower ( Helianthus annuus ) pollen structures onto regenerated silk fibroin films from Bombyx mori . Through a dry process, pollen grains are transformed into continuous, homogeneous patterns over wafer-scale areas, which can be reconfigured via thermally induced capillary action. These geometrically controlled pollen textures are precisely transferred onto one or both sides of the silk films, producing biotextured biopolymer platforms. The hierarchical pollen architecture imparts exceptional surface properties that surpass those of existing natural or synthetic analogs, while preserving the intrinsic advantages of silk fibroin, including recyclability and biodegradability. This approach, decoupling and reintegrating fundamental natural elements at both compositional and structural levels, opens pathways for combining diverse bioresources to realize sustainable materials with enhanced versatility.